O dever de Rousseau ou deixando Berenice: a propósito do Prefácio da Carta a d'Alembert [Rousseau's duty, or leaving Berenice: on the Preface to the Letter to d'Alembert] - Viana Leite, Rafael de Araújo e (Princípios: Revista de Filosofia (UFRN), 2017)
O presente artigo tem por objetivo analisar o Prefácio da Carta a d’Alembert, de Jean-Jacques Rousseau, obra publicada em 1758. Para além da crítica ao teatro efetuada pelo filósofo, tentarei explicitar o registro em que a obra se insere, mostrando a ligação entre literatura, sentimento e política na qual desde o início da Carta a d’Alembert Rousseau parece se engajar. Para tanto, aproximarei a postura do filósofo genebrino à de dois personagens dramáticos do teatro clássico francês, estratégia que parece interessante se pensarmos na polêmica motivada pela obra e, também, na ausência de comentários consagrados exclusivamente ao Prefácio. [The goal of the present article is to analyze the Preface to the Letter to d’Alembert, written by Jean-Jacques Rousseau and published in 1758. Beyond the criticism against the theater made by the philosopher, I will try to clarify what is the work’s register by showing the connection among literature, feeling and politics and the work he seems to be engaged to from its beginning. In order to do so, I will compare Rous-seau’s posture with two dramatic characters from the French classical theater. This strategy seems interesting if we consider the polemic moti-vated by the mentioned work and also the lack of studies dedicated exclu-sively to its Preface.]